Triboelectric energy harvester - Teo, Tee Hao (Nanyang Technological University, 2020)
Triboelectric Nanogenerators (TENG) can be utilized to harvest possibly the largest abundant free energy, coined as ‘blue energy’. This project aims to look at single electrode TENGs to harvest energy from flowing water in the application of tubes used for transporting water. The parameters that would affect the output of the device and finally the optimization of the parameters to give the highest possible output. This is in hope to explore this technology and extending its application in harvesting energy. The materials used for this are Polyvinylchloride (PVC), Polyethylene Terephthalate (PET) films and PVC pipes. The films are rolled to form tubes with the same dimensions as the commercially use PVC pipes, after which modifications were made accordingly to study the effects of changing the parameters; surface area, turbulent flow, roughness and type of liquid medium. The water flow was kept at a constant 10ml/s using a rotary pump and measurement done by a Tektronix electric oscilloscope. The results yielded were PET film gave the best output, while at 800 grit size and using salt water gave the best outputs for varying parameters. Finally, changing the laminar flow also produce interesting results. Though optimization of the parameters using a simple PVC film (50cm2) prepared with the 800 grit size sandpaper and using saltwater as the medium, the highest output generated was 50 volts, 0.001152 mA giving us power of 0.01152 Watt/m2. However, there is still a need to simulate the experiment on a larger scale as results shown in this project that a direct increase in the parameter does not equals to a direct increase in output. And if we were to be able to have success with recycled plastic as well, it would surely be desirable.